Sulfur Dioxide Inhibition of Photosynthesis in Isolated Spinach Chloroplasts - Silvius, John E. (1975)
Photosynthetic oxygen evolution by isolated spinach (Spinacia oleracea L.) chloroplasts approached complete inhibition in the presence of a 5 mm concentration of sulfur dioxide. A similar inhibition was observed in the presence of equimolar concentrations of bisulfite ions, suggesting a parallel mode of action. In contrast, an equimolar concentration of sulfite ions was markedly less inhibitory and sulfate ions caused negligible inhibition of apparent photosynthesis. The mode of action of sulfur dioxide and related sulfur anions in inhibiting photosynthesis was found to be essentially independent of direct hydrogen-ion effects. Supplements of inorganic pyrophosphate lessened the inhibition of oxygen evolution caused by sulfur dioxide and the sulfur anions. Sulfur dioxide and the sulfur anions were almost equally effective in inhibiting cyclic and noncyclic photophosphorylation in chloroplast suspensions. However, the extent of the inhibition of these photosynthetic reactions does not appear sufficient to account for the inhibition of photosynthetic oxygen evolution by sulfur dioxide.